Analisis Pembelajaran IPS di Kelas Tinggi Menggunakan Model Problem Based Learning pada Materi Keberagaman di Indonesia - Neng Ani; Nur Laeli Asyahidah; Tin Rustini (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this study is to provide specifics regarding the application of the Problem-Based Learning (PBL) model in upper-level Social Sciences courses, particularly when it comes to content related to diversity in Indonesia. A qualitative research method through literature review is the research strategy that is being applied. This study focuses only on giving a broad picture of how the Problem Based Learning paradigm is being used in Indonesian elementary schools to teach students about diversity. The results of this study show that a large body of prior research has demonstrated the efficacy of the Problem Based Learning paradigm in the context of social studies instruction at the elementary school level, particularly when it comes to teaching materials on diversity in Indonesia.